IBN KHALDUN'S PHILOSOPHY OF ECONOMICS: BIBLIOMETRIC ANALYSIS AND DESCRIPTIVE QUALITATIVE STUDIES: Bibliometric Analysis and Descriptive Qualitative Studies - Wahyu Hidayat; Syaripudin Hidayat (Yayasan Adra Karima Hubbi, 2026)
The purpose of this study is to see how Ibn Khaldun's philosophy of economics evolved from scientific publications published from 2019 to 2024. In addition, using bibliometric methods and descriptive qualitative analysis, this study will also investigate the conceptual structure of Ibn Khaldun's thought. The Publish or Perish (PoP) software, which has an initial count of 200 articles, uses Google Scholar to obtain research data. To perform bibliometric analysis, VOSviewer is used to observe the relevance of keywords and the tendencies of the research theme. Qualitative analysis shows that Ibn Khaldun's economic thought has an ontological, epistemological, and axiological structure that is coherent and relevant to the development of modern Islamic economics. The results of the analysis show that his thinking is predominantly associated with Islamic economics and Islam as a normative foundation. This study shows that there has been variation in research on how the philosophy of economics developed systematically and integratively based on Ibn Khaldun's thought.